Gait Speed and Variability for Usual Pace and Pedestrian Crossing Conditions in Older Adults Using the GAITRite Walkway. (3rd December 2015) - Brown, Kristin C.; Hanson, Heather M.; Firmani, Flavio; Liu, Danmei; McAllister, Megan M.; Merali, Khalil; Puyat, Joseph H.; Ashe, Maureen C.
Objectives: To determine gait characteristics of community-dwelling older adults at different speeds and during a crosswalk simulation.Methods: Twenty-two older adults completed walking trials at self-selected slow, usual, and fast paces, and at a crosswalk simulation, using the GAITRite walkway. These objective measures were complemented by self-report health and mobility questionnaires.Results: Gait speeds at self-selected slow, usual, and fast paces were 98.7 (18.1) cm/s, 140.9 (20.4) cm/s, and 174.0 (20.6) cm/s, respectively, and at simulated crosswalk conditions was 144.2 (22.3) cm/s. For usual pace, right step length variability was 2.0 (1.4) cm and step time variability was 13.6 (7.2) ms, compared with 2.4 (1.3) cm and 17.3 (9.7) ms, respectively, for crosswalk conditions.Discussion: Our sample of healthy older adults walked at a speed exceeding standards for crossing urban streets; however, in response to a crosswalk signal, participants adopted a significantly faster and more variable gait.